Expiratory muscle strength training for radiation‐associated aspiration after head and neck cancer: A case series. (22nd August 2017) - Hutcheson, Katherine A.; Barrow, Martha P.; Plowman, Emily K.; Lai, Stephen Y.; Fuller, Clifton David; Barringer, Denise A.; Eapen, George; Wang, Yiqun; Hubbard, Rachel; Jimenez, Sarah K.; Little, Leila G.; Lewin, Jan S.
Abstract : Objective/Hypothesis: Expiratory muscle strength training (EMST) is a simple, inexpensive, device‐driven exercise therapy. Therapeutic potential of EMST was examined among head and neck cancer survivors with chronic radiation‐associated aspiration. Study Design: Retrospective case series. Methods: Maximum expiratory pressures (MEPs) were examined among n = 64 radiation‐associated aspirators (per penetration–aspiration scale score ≥ 6 on modified barium swallow). Pre–post EMST outcomes were examined in a nested subgroup of patients (n = 26) who enrolled in 8 weeks of EMST (25 repetitions, 5 days/week, 75% load). Nonparametric analyses examined effects of EMST on the primary endpoint MEPs. Secondary measures included swallowing safety (Dynamic Imaging Grade of Swallowing Toxicity [DIGEST]), perceived dysphagia (M.D. Anderson Dysphagia Inventory [MDADI]), and diet (performance status scale for head and neck cancer patients [PSSHN]). Results: Compared to sex‐matched published normative data, MEPs were reduced in 91% (58 of 64) of aspirators (mean ± standard deviation: 89 ± 37). Twenty‐six patients enrolled in EMST and three patients withdrew. MEPs improved on average 57% (87 ± 29 to 137 ± 44 cm H2 O, P < 0.001) among 23 who completed EMST. Swallowing safety (per DIGEST) improved significantly ( P = 0.03). Composite MDADI scores improved post‐EMST (pre‐EMST: 59.9 ± 17.1, post‐EMST: 62.7 ± 13.9, P = 0.13). PSSHN diet scores did not significantly change. Conclusion: MEPs were reduced in chronic radiation‐associated aspirators relative to normative data, suggesting that expiratory strengthening could be a novel therapeutic target to improve airway protection in this population. Similar to findings in neurogenic populations, these data also suggest improved expiratory pressure‐generating capabilities after EMST and translation to functional improvements in swallowing safety in chronic radiation‐associated aspirators. Level of Evidence: 4. Laryngoscope, 128:1044–1051, 2018